Sanghuang Tongxie Formula Ameliorates Insulin Resistance in Drosophila Through Regulating PI3K/Akt Signaling - Cao, Xuqing; La, Xiaojin; Zhang, Biwei; Wang, Zhigang; Li, Yinghong; Bo, Yanping; Chang, Hong; Gao, Xiujuan; Tian, Chunyu; Wu, Chenxi; Li, Ji-an (Frontiers in Pharmacology, 2022)
Insulin resistance (IR) is a pivotal pathological characteristic that affects the occurrence and development of type 2 diabetes mellitus (T2DM). Thus, the effective control of IR is of great significance for diabetes prevention and treatment. Traditional Chinese medicine (TCM) represents a valuable tool handed down to the world by the Chinese nation, and has a long history of use for diabetes clinical therapy. In this study, we focused on a self-drafted TCM-patented formula, Sanghuang Tongxie Formula (SHTXF), which exhibits clinical efficacy in the treatment of diabetes. To explore the effect and molecular mechanism of SHTXF on IR in vivo, Drosophila melanogaster was used and a (Collagen) Cg>InRK1409A diabetic IR fly model was established. SHTXF water extract was found to contribute to carbohydrate clearance from the circulating system by converting it into triglycerides (TAG), not glycogen, for nutrient storage. In addition, SHTXF activated phosphatidylinositol 3-kinase (PI3K) activity and improved protein kinase B (PKB, also termed Akt) phosphorylation. Finally, SHTXF promoted Drosophila Forkhead Box O (dFoxO) cytoplasmic localisation and inhibited its transcriptional activity. Taken together, these findings not only highlight the positive role of SHTXF in ameliorating IR via the PI3K/Akt pathway, but also provide potential drug targets and key insights for use in T2DM clinical treatment strategies.